The effect of varying levels of salinity and organic matter on the growth and composition of lab-lab - Arifin, Syamsul
A 45 days culture of lab-lab to determine its growth and composition in 4 levels of salinity ( S1 and 0 ppt, S2 = 10 ppt, S3 = 20 ppt and S4 = 30 ppt) and two levels of organic matter (OM1 = 5% and OM2 = 10%) was conducted using experimental plots (1 x 1 x 0.4 m) at the Brackishwater Aquaculture Center, University of the Philippines in the Visayas, Leganes, Iloilo. The study wasconducted in a 4 x 2 factorial arrangement in a completely randomized design (CD) with 3 replicates. The desired levels of organic matter were attained by applying chicken manure and the salinity by mixing the fresh and brackishwater. Organic matter levels of the soil considerably affected the chemical properties of water and soil. Higher organic matter levelsshowed increase in available phosphorus, reactive phosphorus and ammonia-nitrogen concentration, but a decrease in water and soil pH. Salinity did not generally affect the levels of ammonia, reactive phosphorus and the pH of soil. However, o ppt salinity had slightly higher water pH. The ash free dry weight of lab-lab was significantly higher in treatments with 5%organic matter than in treatments with 10% organic matter. The growth of lab-lab at 0 ppt salinity was significantly lower than 10 ppt, 20 ppt and 30 ppt. For the entire culture period the correlation coefficients between ash free dry weight lab-lab and most soil and water properties monitored (ammonia-nitrogen, reactive phosphorus, available phosphorus, waterpH, soil pH and total nitrogen) were low. The reactive phosphorus showed high concentration during 1st to 3rd weeks, and water pH during the 5th to 7th weeks. Generally, total primary productivity, as reflected by dissolved oxygen, was evidently high in treatments with 5% organic matter content. The levels of significance using Duncan's multiple range test showed irregular trends with time. The dominant biota found in lab-lab were chlorella and Synedra for the plant, and Ciliata, Flagellata and Branchiopoda for the animal.